Sparking technological innovation through CASS educational entrepreneurship initiative - Friebe, Michael; Chen, Jie; Rokhani, Fakhrul Zaman (Institute of Electrical and Electronics Engineers, 2024)
Recognizing the increasing relevance of entrepreneurship skillsets to engineers, CASS launched an initiative to educate on entrepreneurship with technology solutions aligned with CAS Society's visions. In this special issue, this article introduces the motivation, course setup, and the results of an intensive six-week hybrid course stimulating entrepreneurial thinking. The course was based on a novel iterative and agile innovation framework designed to lead up to the BIOCASS 2023 conference in Toronto, inviting the best proposals for an in-person presentation. The learners confirmed a changed mindset towards innovation generation.